A Comparative analysis of the explanatory power of the CAPM and the Fama-French three-factor model on cross-sectional variation of returns on stocks trading on the Official market of the Macedonian Stock exchange - Fatmir Besimi; Ana Bisheva (Economy, Business and Development: An International Journal (EB&D), 2021)
The amount of literature on factors that explain the cross-sectional variation in average returns is vast, however, the majority of these papers attempt to explain the variation of returns in developed and emerging markets. In that sense, the literature lacks sufficient evidence regarding the variation of returns of frontier markets. The Republic of North Macedonia is considered to be a frontier market and in this paper we aim to empirically test the ability of the Capital Asset Pricing model and the Fama-French three factor model in explaining the cross-sectional variations of stock returns of securities trading on the Macedonian stock exchange. The empirical study is based on monthly returns from January 2011 to April 2021. Additionally, we use annual data obtained from the financial statements of the analysed companies included in this study. Using OLS time series regression we find that both models have limited explanatory power of the cross-sectional variation in expected returns on the Macedonian Stock exchange. The study shows that only the size factor exhibits some limited explanatory power regarding stock returns. Based on the comparative analysis the Fama-French three-factor model describes the variation of returns on the MSE much better than the Capital Asset Pricing Model.
Keywords: G12; G14; G11; G15; 330; asset pricing; CAPM; cross-sectional variation; Fama-French three-factor model; Macedonian Stock Exchange